2011
DOI: 10.1128/jvi.00219-11
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Evolutionary History of Reassortant H9N2 Viruses with Potential Human Health Implications

Abstract: Avian influenza viruses of the H9N2 subtype have seriously affected the poultry industry of the Far andMiddle East since the mid-1990s and are considered one of the most likely candidates to cause a new influenza pandemic in humans. To understand the genesis and epidemiology of these viruses, we investigated the spatial and evolutionary dynamics of complete genome sequences of H9N2 viruses circulating in nine Middle Eastern and Central Asian countries from 1998 to 2010. We identified four distinct and cocircul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
160
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 48 publications
9
160
1
Order By: Relevance
“…Although nearly all RNA viruses seem to experience very rapid evolutionary change-usually expressed as rates of nucleotide substitution per site-far lower rates are observed in some large double-stranded DNA (dsDNA) viruses. For example, the nucleotide substitution rates for variola virus and herpes simplex virus (dsDNA) have been reported to be as low as 9.32 Â 10 -6 and 3 Â 10 29 substitutions per site per year, respectively [6,7], and hence between three to six orders of magnitude lower than that of influenza virus A (negative-sense singlestranded RNA; 2ssRNA) at 4.1 Â 10 23 substitutions per site per year [8]. Overall, most RNA viruses seem to exhibit evolutionary rates of around 10 23 to 10 24 substitutions per site per year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although nearly all RNA viruses seem to experience very rapid evolutionary change-usually expressed as rates of nucleotide substitution per site-far lower rates are observed in some large double-stranded DNA (dsDNA) viruses. For example, the nucleotide substitution rates for variola virus and herpes simplex virus (dsDNA) have been reported to be as low as 9.32 Â 10 -6 and 3 Â 10 29 substitutions per site per year, respectively [6,7], and hence between three to six orders of magnitude lower than that of influenza virus A (negative-sense singlestranded RNA; 2ssRNA) at 4.1 Â 10 23 substitutions per site per year [8]. Overall, most RNA viruses seem to exhibit evolutionary rates of around 10 23 to 10 24 substitutions per site per year [9].…”
Section: Introductionmentioning
confidence: 99%
“…H9N2 is a predominant subtype of AIVs circulating in poultry farms in Asia and the Middle East and has caused substantial economic losses over the past decade (3)(4)(5)(6)(7)(8)(9). Although a large amount of H9N2 vaccines, including inactivated and vectored vaccines, have been used in areas of endemicity, outbreaks caused by H9N2 AIVs are still not efficiently controlled.…”
mentioning
confidence: 99%
“…This suggests a contribution from an H9N2 virus to the internal genes of the HPAI H5N1 virus that infected humans (10). Genetic drift has caused distinct lineages of H9N2 virus to emerge in Eurasia, and between three and five Eurasian H9N2 lineages have been proposed (11)(12)(13). Recent data have shown that H9N2 reassortment, together with adaptive mutations, can generate novel reassortant viruses that are more transmissible and more pathogenic in mammalian models than the parental viruses (14,15).…”
mentioning
confidence: 99%